2008
DOI: 10.1016/j.ijcard.2008.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage roles following myocardial infarction

Abstract: Following myocardial infarction (MI), circulating blood monocytes respond to chemotactic factors, migrate into the infarcted myocardium, and differentiate into macrophages. At the injury site, macrophages remove necrotic cardiac myocytes and apoptotic neutrophils; secrete cytokines, chemokines, and growth factors; and modulate phases of the angiogenic response. As such, the macrophage is a primary responder cell type that is involved in the regulation of post-MI wound healing at multiple levels. This review su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
267
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(281 citation statements)
references
References 165 publications
11
267
0
3
Order By: Relevance
“…originate from circulating blood monocytes, which are derived from CD34+ bone marrow progenitors [20]. The conversion of monocytes into macrophages begins with their adhesion to the vessel wall.…”
Section: Macrophage Infiltration-macrophagesmentioning
confidence: 99%
“…originate from circulating blood monocytes, which are derived from CD34+ bone marrow progenitors [20]. The conversion of monocytes into macrophages begins with their adhesion to the vessel wall.…”
Section: Macrophage Infiltration-macrophagesmentioning
confidence: 99%
“…Following MI, resident and recruited macrophages remove necrotic and apoptotic cells, secrete cytokines, and modulate angiogenesis at the infarct site (1). As such, the macrophage is a primary responder cell involved in the regulation of post-MI infarct wound healing at multiple levels (2). According to recent studies, different subsets of macrophages are responsible for these different activities; during the early inflammatory phase (phase 1), proinflammatory macrophages dominate the injury site and phagocytose apoptotic/necrotic myocytes and other debris, whereas during inflammation resolution (phase 2), the dominant subsets are the reparative macrophages, which propagate infarct repair (3,4).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that AMI elicits inflammatory and innate immune responses, generates oxidative stress/reactive oxygen species (ROS), and initiates the complement cascade 26,[33][34][35] which, in turn, would damage the remote myocardium. 26) In the current study, even at day 90 after AIM, the inflammatory response/oxidative stress at the gene level (MMP-9), cellular level (CD40+ cells), and protein level (oxidized protein) were substantially increased in MI animals compared with those in normal controls.…”
Section: Bmdmsc Transplantation Improved Heart Function -Role Of Immumentioning
confidence: 99%
“…Our findings were comparable to those of previous studies. 26,[33][34][35] Of importance is that these parameters were markedly reduced in MI animals with BMDMSC treatment. Conversely, the gene expression of IL-10, an anti-inflammatory/ immune modulator, was remarkably higher in MI animals with BMDMSC therapy than in those without.…”
Section: Bmdmsc Transplantation Improved Heart Function -Role Of Immumentioning
confidence: 99%